SURVEY TINGKAT KEMAMPUAN TEKNIK DASAR BERMAIN BOLA VOLI - Topan Arisandi; Indri Susilawati; Maulidin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
The technical abilities and skills possessed are the most influential factors in volleyball. The problems in this study are: What are the basic technical skills of playing volleyball in seventh grade male students of MTs Nurul Islam Sekarbela Mataram. The sample used consisted of 18 grade VII students. The data collection method used in this study was a survey of the basic techniques of playing volleyball. Such as upper passing, lower pass, serve and smash. Analysis using cumulative percentages. The results of the study 1) Top passings are as follows: for the Special category as much as 6%, for the Very Good category as many as 0%, for the good category for 6%, for the moderate category as much as 33%, for the less category as much as 55%, and for the under category as much as 0%, 2 ) Passing below is as follows: for the Special category as much as 0%, for the Very Good category as much as 17%, for the good category as much as 28%, for the moderate category as much as 38%, for the less category as much as 17%, and for the under category as much as 0%, 3) Service as the following: for the Special category as much as 0%, the Very Good category as much as 0%, the good category 6%, the moderate category as much as 17%, the less category as much as 83%, and for the very poor category as much as 0%, 4) Smash as follows: for the category Special was 0%, Very Good category was 0%, good category was 6%, moderate category was 22%, Poor category was 72%, and very poor category was 0%. The conclusion from the research results is that extracurricular activitiesdone is still not optimal, this is due to the results of the analysis data regarding the basic techniques of playing volleyball for students at MTs Nurul Islam Sekaarbela Mataram City are in the medium category. The suggestions that can be given are Volleyball extracurricular students should further enhance the exercise program in order to master and develop the basic techniques of playing volleyball, increase the frequency of training, the trainer must further improve kepelatihannya in order to help students develop abilities the basics of playing volleyball in its training program. Kemampuan teknik dan ketrampilan yang dimiliki merupakan faktor yang paling berpengaruh dalam permainan bola voli. Permasalahan dalam penelitian ini adalah: Bagaimanakah keterampilan teknik dasar bermain bola voli pada siswa putra kelas VII MTs Nurul Islam Sekarbela Kota Mataram. Sampel yang digunkan terdiri dari 18 orang siswa kelas VII. Metode pengumpulan data yang digunakan dalam penelitian ini adalah survey teknik dasar bermain voli. Seperti passing atas, pasing bawah, servis dan smash. Analisis dengan menggunakan persentase komulatif. Hasil penelitian 1) Passing atas sebagai berikut: untuk kategori Istimewa sebanyak 6 %, kategori Baik Sekali sebanyak 0 %, kategori baik 6 %, kategori sedang sebanyak 33 %, kategori kurang sebanyak 55 %, dan untuk kategori kurang sekali sebanyak 0 %, 2) Passing bawah sebagai berikut: untuk kategori Istimewa sebanyak 0 %, kategori Baik Sekali sebanyak 17 %, kategori baik 28%, kategori sedang sebanyak 38 %, kategori kurang sebanyak 17 %, dan untuk kategori kurang sekali sebanyak 0%, 3) Service sebagai berikut: untuk kategori Istimewa sebanyak 0%, kategori Baik Sekali sebanyak 0%, kategori baik 6%, kategori sedang sebanyak 17%, kategori kurang sebanyak 83%, dan untuk kategori kurang sekali sebanyak 0%, 4) Smash sebagai berikut: untuk kategori Istimewa sebanyak 0%, kategori Baik Sekali sebanyak 0%, kategori baik 6%, kategori sedang sebanyak 22%, kategori kurang sebanyak 72%, dan untuk kategori kurang sekali sebanyak 0%. Simpulan dari hasil penelitian adalah kegiatan ekstrakurikuler yang dilakukan masih belum maksimal, hal ini di sebabkan karena dari hasil analisis data mengenai teknik dasar bermain bola voli siswa MTs Nurul Islam Sekarbela Kota Mataram masuk dalam kategori sedang. Adapun saran yang dapat diberikan yaitu siswa peserta ekstrakurikuler bola voli harus lebih meningkatkan program latihan agar dapat menguasai dan mengembangkan teknik dasar bermain bola voli, menambah frekuensi latihan, bagi pelatih harus lebih meningkatkan kepelatihannya agar dapat membantu para siswa mengembangkan kemampuan dasar bermain bola voli dalam program latihannya